The Ribosomal Database Project - Olsen, Gary J. (1992)
The Ribosomal Database Project (RDP) compiles ribosomal sequences and related data, and redistributes them in aligned and phylogenetically ordered form to its user community. It also offers various software packages for handling, analyzing and displaying sequences. In addition, the RDP offers (or will offer) certain analytic services. At present the project is in an intermediate stage of development.